Development of Mission and Christian Education GMIM in Minahasa - Meily Meiny Wagiu; A. P.P Undap; Heldy J. Rogahang (Peneliti.net, 2021)
The purpose of this study is to describe the chronology of the development of the mission of evangelism and Christian GMIM education in Minahasa, to study zending biographical narratives, to evaluate and correct the quality of GMIM Christian schools and to design a model for the development of GMIM Christian education in the future. To achieve this goal, a qualitative research method is used with a biographical narrative criticism approach. To collect field data, this research uses observation, interview and documentation study techniques. Based on the results of the research that has been done, it can be concluded that; The foundation stone of the mission of evangelism and Christian education GMIM in Minahasa is Hellendoorn through the method of foster children, the establishment of schools and churches; Education is a shared responsibility of government, church and society. The government together with the Foundation are taking steps to rebuild the GMIM school as a shared responsibility, through the Ministry of Religion, in this case the Directorate General of Christian Community Guidance.